Dentist: Wrist Position, Handgrip Strength, and Body Mass Index Associated with Carpal Tunnel Syndrome in Daily Practice - Annisaa Putri Ariyani; Wita Anggraini; Boedi Oetomo Roeslan; Indrani Sulistyowati (Universitas Malahayati Lampung, 2024)
ABSTRACT Carpal tunnel syndrome (CTS) is one of the most common musculoskeletal disorders affecting dentists and their ability to work. Prolonged work with repetitive flexion and extension of the wrist position and high force may increase the risk of CTS. Exposure to various individual factors (gender, age, work duration, work experience, body mass index), wrist position, and handgrip strength during daily practice may also trigger CTS. To determine whether individual factors, wrist position, and handgrip strength were associated with CTS incidence in dentists. A case-control study in the population of the epidemiological study area. Dentists practicing at the community health center in Tangerang, Banten, agreed to complete the informed consent form. The total population of this present study in the forty-four community health centers in Tangerang was sixty-seven participants. Two participants were excluded due to a history of arthritis and diabetes mellitus. Therefore, only sixty-five participants who met the inclusion criteria were included. The assessment included observation of wrist position, handgrip strength, body mass index, and individual questionnaires (gender, age, work duration, and work experience). The association between these variables and CTS was then analyzed using the chi-squared test. The distribution of CTS among dentists showed that eighteen participants complained of CTS, while forty-seven participants did not. In a case group, the majority of participants complaining of work-related CTS symptoms were female (94.40%). We found that CTS sufferers were over 35 years of age (61.10%), had more than 9 years of work experience (61.10%), and had less than 6 hours of work duration (61.60%). Whereas, 100% of the participants performed wrist position at risk for CTS, 77.80% had weak handgrip strength, and 50% were obese based on body mass index compared to the control group at 80.90%, 4.30%, and 2.10%, respectively. The Chi-square test showed a significant level of wrist position, handgrip strength, and BMI against CTS. CTS is a disease associated with a dentist's wrist position, handgrip strength, and body mass index during dental practice. Keywords: Dentist, Carpal Tunnel Syndrome, Wrist Position, Handgrip Strength, Body Mass Index